2021
DOI: 10.3389/fpls.2021.670965
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Genotype by Environment Interactions for Seed Zinc and Iron Concentration and Iron Bioavailability in Common Bean

Abstract: Iron and zinc malnutrition are global public health concerns afflicting mostly infants, children, and women in low- and middle-income countries with widespread consumption of plant-based diets. Common bean is a widely consumed staple crop around the world and is an excellent source of protein, fiber, and minerals including iron and zinc. The development of nutrient-dense common bean varieties that deliver more bioavailable iron and zinc with a high level of trait stability requires a measurement of the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
(69 reference statements)
6
19
0
Order By: Relevance
“…In summary, the study by Katuuramu et al (2021), appears to be the only published study demonstrating the GxE effect on bean Fe concentration. Most importantly this study is a 2 year "on farm" trial thus demonstrating the variance in Fe concentration that can occur once varieties are released to farmers.…”
Section: Assumption #3: Breeding For High Fe Concentration Is a Trait That Can Be Achieved Through Traditional Breeding And Is Sustainablmentioning
confidence: 80%
See 3 more Smart Citations
“…In summary, the study by Katuuramu et al (2021), appears to be the only published study demonstrating the GxE effect on bean Fe concentration. Most importantly this study is a 2 year "on farm" trial thus demonstrating the variance in Fe concentration that can occur once varieties are released to farmers.…”
Section: Assumption #3: Breeding For High Fe Concentration Is a Trait That Can Be Achieved Through Traditional Breeding And Is Sustainablmentioning
confidence: 80%
“…To illustrate the E and GxE effect on Fe concentration, consider the results illustrated in Figure 3. In this study, Fe concentration of 10 bean varieties grown across 2 consecutive growing seasons in 9 different agroecologies in Uganda is summarized (Katuuramu et al, 2021). The results clearly show high variability across location for any given variety, ∼30-40 µg/g.…”
Section: Assumption #3: Breeding For High Fe Concentration Is a Trait That Can Be Achieved Through Traditional Breeding And Is Sustainablmentioning
confidence: 82%
See 2 more Smart Citations
“…It is worth noting that genotype by environment interaction (GxE) was reported as a factor influencing iron concentration in a variety [ 11 ]. A recent study indicated that seed iron concentration was largely controlled by genotype, location, and the interaction between genotype, location, and season which represented 25.7, 17.4, and 13.7% of phenotypic variation, respectively [ 12 ]. Defining the target population of environments such as sets of farms in which the varieties produced by a breeding program would be grown could lessen GxE effects on iron.…”
Section: Introductionmentioning
confidence: 99%